Interview with Professor Philippe Denis - Van Tonder, Helené (Acta theologica, 2015)
Prof. Philippe Denis is a Senior Professor in History of Christianity at the University of Kwazulu‑Natal. In the 1970s and 1980s, his research focused on the history of the Reformation in Germany, France and The Netherlands, and specifically on issues of confessional development, biblical exegesis, and cultural representations. Over the past two decades, his research focused primarily on the history of indigenous Christianity in southern Africa, along with an interest in oral history. The latter has encouraged him to reflect on issues of memory and resilience, and to found the Sinomlando Centre for Oral History and Memory Work in Africa.